Нові та рідкісні для Лівобережної України види лишайників із крейдяних відслонень - Громакова, А.Б. (Український ботанічний журнал, 2013)
Выявлены местонахождения 16 новых и редких для Левобережной Украины видов лишайников, собранных на меловых обнажениях в бассейне реки Сиверский Донец. Это Arthonia calcarea (Turner ex Sm.) Ertz & Diederich, Caloplaca limonia Nimis & Poelt, C. phlogina (Ach.) Flagey, Catillaria lenticularis (Ach.) Th. Fr., Rinodina terrestris Tomin, Squamarina cartilaginea (With.) P. James, Thrombium epigaeum (Pers.) Wallr., Xanthoria mediterranea Giralt, Nimis & Poelt приводятся впервые для Левобережной Украины. Среди видов, занесенных в «Червону книгу України» (2009), для Leptogium schraderi (Bernh.) Nyl. и Squamarina cartilaginea указаны новые местонахождения, а для Circinaria hispida (Mereschk.) A. Nordin, S. Savić & Tibell подтвержден локалитет в Харьковской обл. The localities of 16 new and rare species of lichens for the Left-Bank part of Ukraine are cited. The species were collected from the cretaceous outcrops in the basin of the Siversky Donets River. Among them Arthonia calcarea (Turner ex Sm.) Ertz & Diederich, Caloplaca limonia Nimis & Poelt, C. phlogina (Ach.) Flagey, Catillaria lenticularis (Ach.) Th. Fr., Rinodina terrestris Tomin, Squamarina cartilaginea (With.) P. James, Thrombium epigaeum (Pers.) Wallr., Xanthoria mediterranea Giralt, Nimis & Poelt are reported for the first time for the Left-Bank part of Ukraine. New data on distribution of the red-listed lichen species, Leptogium schraderi (Bernh.) Nyl., Squamarina cartilaginea, Circinaria hispida (Mereschk.) A. Nordin, S. Savić & Tibell, are provided.